LINGUISTIC AND TRANSLATION FEATURES OF TRADE DOCUMENTS IN UZBEK, ENGLISH, AND RUSSIAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The development of international trade relations and globalization processes has significantly increased the importance of translation in cross-border communication. Trade documents such as contracts, invoices, customs declarations, certificates, and financial agreements play a key role in regulating economic cooperation between countries. Since these documents combine legal and economic content, their translation requires high linguistic accuracy, terminological consistency, and professional knowledge.\
Keywords: This research focuses on the linguistic and translation features of trade documents in Uzbek, English, and Russian. It analyzes lexical, grammatical, and stylistic characteristics of trade discourse and identifies the main challenges faced by translators in this field. The study also examines translation strategies used to achieve functional equivalence and legal accuracy.